Considering treatment-as-prevention scale-up for Australian prisons: a qualitative sub-study of expert stakeholders from the Australian 'surveillance and treatment of prisoners with hepatitis C' project (SToP-C) - Jake Rance; Lise Lafferty; Carla Treloar; the SToP-C Study Group (BMC, 2021)
Abstract Background With direct-acting antivirals dramatically reshaping the public health response to the hepatitis C virus (HCV), prisons are set to play a critical role in elimination efforts. Despite the theoretical demonstration of HCV treatment-as-prevention in prison in mathematical modeling, limited empirical data exist. The Australian 'Surveillance and Treatment of Prisoners with Hepatitis C' project (SToP-C) is the world's first trial of HCV treatment-as-prevention in prison. Drawing on interviews with HCV expert stakeholders, this paper explores the factors respondents identified as crucial to the success of future scale-up. Accounting for such perspectives matters because of the influence expert discourse has in shaping implementation. Methods Semi-structured interviews were conducted with nineteen HCV experts working across key policy, advocacy, research and clinical dimensions of the Australian HCV response. Data were coded using qualitative data management software (NVivo 11). Analysis proceeded via a hybrid deductive and inductive approach. Results Notwithstanding concerns regarding the lack of primary prevention in Australian prisons, stakeholders reported broad levels of support for the intervention and for the future scale-up of HCV treatment. A number of considerations, both external and internal to the prison system, were identified as key. The principal external factor was an enabling political-cum-policy environment; internal factors included: obtaining support from prisons' executive and custodial staff; promoting health within a security-first institutional culture; allocating time for treatment within prisoners' tightly regulated schedules; ensuring institutional stability during treatment given the routine movement of prisoners between prisons; prioritizing the availability of retreatment given the paucity of primary prevention; and securing sufficient clinical space for treatment. Conclusion The challenges to implementation are considerable, ranging from macrolevel concerns to in-prison logistical matters. Nonetheless, we argue that prisons remain an obvious setting for treatment scale-up, not only for prevention and potential elimination benefit, but for the treatment opportunities they afford a socially disadvantaged and underserved population. While noting widespread concerns among respondents regarding the paucity of primary prevention in Australian prisons, results indicate broad levels of support among expert stakeholders for HCV treatment scale-up in prison.